2009
DOI: 10.1007/s11515-009-0027-4
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization, and antibacterial activity of oleic acid-grafted chitosan oligosaccharide nanoparticles

Abstract: An oleic acid-grafted chitosan oligosaccharide (CSO-OA) with different degrees of amino substitution (DSs) was synthesized by the 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC)-mediated coupling reaction. Fourier transform infrared spectroscopy (FT-IR) suggested the formation of an amide linkage between amino groups of chitosan oligosaccharide and carboxyl groups of oleic acid. The critical aggregation concentrations (CACs) of CSO-OA with 6%, 11%, and 21% DSs were 0.056, 0.042, and 0.028 mg$mL -1 , respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 27 publications
1
33
0
Order By: Relevance
“…The coupling reaction between the amino group of CSO and the carboxyl group of OA was confirmed by infrared spectrum in our previous study [27]. The morphological characteristic of the OA-g-CSO nanoparticles evaluated by TEM was shown in Fig.…”
Section: Characterization Of Oa-g-cso Nanoparticlessupporting
confidence: 64%
See 1 more Smart Citation
“…The coupling reaction between the amino group of CSO and the carboxyl group of OA was confirmed by infrared spectrum in our previous study [27]. The morphological characteristic of the OA-g-CSO nanoparticles evaluated by TEM was shown in Fig.…”
Section: Characterization Of Oa-g-cso Nanoparticlessupporting
confidence: 64%
“…As reported in our previous study [27], OA-g-CSO was synthesized via the reaction of the carboxyl group of OA with the primary amino group of CSO mediated by EDC.…”
Section: Methodsmentioning
confidence: 99%
“…As hydrophobic molecule, pyrene is apt to concentrate in the hydrophobic domains of amphipathic molecules. 8,38 The intensity ratio of the third peak (at 384 nm) and the first peak (at 373 nm) I 3 /I 1 is regularly utilized to study the change in environmental polarity based upon the association of amphipathic molecules in solutions. 39,40 As soon as the micellization of Lac-OCH, the hydrophobic microdomain attributed to oleoyl chain will be occupied by pyrene, 1 causing the increasing of the intensity ratio I 3 /I 1 .…”
Section: Self-assembly Behavior Of Lac-ochmentioning
confidence: 99%
“…Chitosan, a native cationic polymer consisting of D-glucosamine and N-acetyl-D-glucosamine 4,5 linked by b-(1!4) glycosidic bond, [6][7][8] is harvested from the exoskeleton of crustaceans and insects as chitin and goes through alkaline deacetylation. 9 Chitosan is known to be a favorable pharmaceutical material because of its excellent biocompatibility, biodegradability, low immunogenicity, and biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Chromium is dominantly removed by surface reduction of Cr(VI) to Cr(III) followed by adsorption of Cr(III) [14]. Recent advances in nanotechnology have suggested that nanoparticles can be explored for applications in water and wastewater treatment [15].…”
Section: Introductionmentioning
confidence: 99%